Learning Innovation in Malaysia with a System Thinking Approach (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Learning process innovation with a system thinking approach can improve the quality of learning through analysis of the relationship between learning problem variables and problem-solving. The purpose of this study to implement a system thinking approach to improving creative thinking, and problem-solving skills by thinking in a systemic way that can be developed in the learning process. Community Service uses a descriptive method with a qualitative approach. Data collection techniques are carried out by observing and documenting students in the learning process. System thinking in the learning process provides an overview of the interrelationships of problems in learning so that it can be used as a basis for developing problem-solving strategies through learning innovation. Learning Innovation with a System Thinking approach through interactive and student-centered learning can improve creative thinking skills, and problem-solving abilities to identify and find solutions to problems in the learning process.